2015
DOI: 10.1152/jn.00870.2013
|View full text |Cite
|
Sign up to set email alerts
|

Functional link between the hypocretin and serotonin systems in the neural control of breathing and central chemosensitivity

Abstract: Corcoran AE, Richerson GB, Harris MB. Functional link between the hypocretin and serotonin systems in the neural control of breathing and central chemosensitivity. J Neurophysiol 114: 381-389, 2015. First published April 15, 2015 doi:10.1152/jn.00870.2013.-Serotonin (5-HT)-synthesizing neurons of the medullary raphe are putative central chemoreceptors, proposed to be one of potentially multiple brain stem chemosensitive cell types and loci interacting to produce the respiratory chemoreflex. Hypocretin-synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…More recently, Lavezzi et al (44) provided evidence of decreased orexin receptor 1 expression in the Kolliker-Fuse nucleus of SIDS cases. Others have shown important interactions between the orexin and serotonin system on the control of breathing; for example, the inhibitory effects of orexin receptor blockade on hypoglossal burst frequency are significantly reduced in mice lacking 5-HT neurons (18). These findings, along with our current data, raise the intriguing possibility that orexinergic defects predispose infants to SIDS because they compromise the serotonergic control of breathing in a critical period of postnatal development.…”
Section: Orexin Defects May Predispose Infants To Sidssupporting
confidence: 76%
See 2 more Smart Citations
“…More recently, Lavezzi et al (44) provided evidence of decreased orexin receptor 1 expression in the Kolliker-Fuse nucleus of SIDS cases. Others have shown important interactions between the orexin and serotonin system on the control of breathing; for example, the inhibitory effects of orexin receptor blockade on hypoglossal burst frequency are significantly reduced in mice lacking 5-HT neurons (18). These findings, along with our current data, raise the intriguing possibility that orexinergic defects predispose infants to SIDS because they compromise the serotonergic control of breathing in a critical period of postnatal development.…”
Section: Orexin Defects May Predispose Infants To Sidssupporting
confidence: 76%
“…Using a brainstemspinal cord preparation from neonatal rats, Sugita et al (19) showed that application of exogenous orexin B, the second isoform of orexin that binds preferentially to OxR2, increased the rate of bursting of cranial nerve IV, with no change in This group also recorded from individual respiratory neurons and found that orexin B increased the discharge frequency of inspiratory neurons (19). A physiological role for orexin in respiratory rhythm generation in the early postnatal period is also supported by data from Corcoran et al (18), who showed that OxR1 blockade reduced hypoglossal nerve burst frequency in medullary slices from neonatal mice. The Kolliker-Fuse (KF) nucleus is also heavily innervated by orexinergic fibers (29), and may serve as a relay site for peripheral chemoreflex afferent inputs via the commissural and medial subregions of the nucleus of the solitary tract (30).…”
Section: Potential Mechanisms Underlying Orexin's Contribution To Eupneamentioning
confidence: 88%
See 1 more Smart Citation
“…This consensus contrasts with the results from studies addressing the role of ORX in the regulation of respiratory function in early life. The variability of the results is surprising considering that research has been limited to rats and mice using reduced preparations both in vivo and ex vivo (Corcoran et al, 2010(Corcoran et al, , 2015Loiseau et al, 2019;Sugita et al, 2014). For instance, Loiseau et al (2019) reported that bath application of ORX-A (10 −3 to 10 −2 µmol l −1 ) onto diencephalon-brainstem-spinal cord preparations augments basal phrenic burst frequency and potentiates the fictive breathing response to CO 2 and H + .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Loiseau et al (2019) reported that bath application of ORX-A (10 −3 to 10 −2 µmol l −1 ) onto diencephalon-brainstem-spinal cord preparations augments basal phrenic burst frequency and potentiates the fictive breathing response to CO 2 and H + . Conversely, application of ORX-A (0.3 µmol l −1 ) onto medullary slices reduces fictive breathing frequency, increases tonic hypoglossal discharge, but has no effect on the response to CO 2 and H + (Corcoran et al, 2015). The ORX system undergoes important anatomical and functional changes during the transition from fetal to extra-uterine life (Ogawa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%